Association of Chest Radiograph with Community Acquired Pneumonia among the Children Admitted in Dhaka Shishu Hospital (Delta Medical College Journal, 2019)
Background: Community-acquired pneumonia (CAP) is an infectious disease and common reason for hospitalization of children throughout the world. There are few published data about radiological findings and their relationship with community-acquired pneumonia (CAP) severity.Objective: This study was conducted to evaluate radiological findings in children with community acquired pneumonia (CAP) of different severity.Materials and method: A prospective study was conducted in the department of Paediatric Respiratory Medicine (Pulmonology) in Dhaka Shishu Hospital from November 2016 and April 2017. A total number of 35 children of 1 month to 10 years, who were admitted with cough or respiratory difficulty and radiological pneumonia were included in this study.Results: Majority of the study participants 18 (51.43%) were infants with a male preponderance. The most common symptom was cough (94.29%) followed by fever (82.86%) and respiratory distress (42.86%). Crepitation (54.29%), tachypnoea (42.86%) and chest indrawing (28.57%) were the most common signs. Out of total 35 children 17 (48.57%) cases had pneumonia and 18 (51.43%) cases had severe pneumonia. Among chest X-rays, severe pneumonia had greatest frequency of primary end point consolidation (PEP) on right side (n=10, 55.55%), right infiltrates (n=5, 27.78%), bilateral infiltrates (n=2, 11.11%) followed by right sided pleural effusion (n=3, 16.67%) and pneumothorax (n=2, 11.11%). There was no association found between CAP severity and presence of radiological findings of pneumonia.Conclusion: This study shows that severe CAP may not always be associated with positive radiological findings. This finding may be taken into consideration during the diagnosis and management of CAP.Delta Med Col J. Jan 2019 7(1): 21-25